2012
DOI: 10.1063/1.3703602
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum disulphide/titanium dioxide nanocomposite-poly 3-hexylthiophene bulk heterojunction solar cell

Abstract: Demonstration of hybrid bulk heterojunction (BHJ) solar photovoltaic cell employing molybdenum disulfide (MoS2)/titanium dioxide (TiO2) nanocomposite (∼15 μm thick) and poly 3-hexylthiophene (P3HT) active layers is presented in this letter. The dominant Raman peak at 146 cm−1 confirmed TiO2, while two other peaks observed at 383 cm−1 and 407 cm−1 asserted MoS2 in the nanocomposite film. The demonstrated BHJ solar cell, having a stacked structure of indium tin oxide/TiO2/MoS2/P3HT/gold, exhibits a short circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(93 citation statements)
references
References 25 publications
4
87
2
Order By: Relevance
“…Lee et al 144 have demonstrated that single-and double-layer MoS 2 , with respective bandgap energies of 1.8 and 1.65 eV, are effective for detecting green light, and triple-layer MoS 2 with a bandgap of 1.35 eV is well suited for red light. A bulk heterojunction solar cell made from TiO 2 nanoparticles, MoS 2 atomic layer nanosheets and poly(3-hexylthiophene) (P3HT) was recently demonstrated with 1.3% photoconversion efficiency 145 . Similarly, electrochemical solar cells with TiO 2 were sensitized with WS 2 , which acts as a stable, inorganic absorber material 146,147 .…”
Section: Optoelectronicsmentioning
confidence: 99%
“…Lee et al 144 have demonstrated that single-and double-layer MoS 2 , with respective bandgap energies of 1.8 and 1.65 eV, are effective for detecting green light, and triple-layer MoS 2 with a bandgap of 1.35 eV is well suited for red light. A bulk heterojunction solar cell made from TiO 2 nanoparticles, MoS 2 atomic layer nanosheets and poly(3-hexylthiophene) (P3HT) was recently demonstrated with 1.3% photoconversion efficiency 145 . Similarly, electrochemical solar cells with TiO 2 were sensitized with WS 2 , which acts as a stable, inorganic absorber material 146,147 .…”
Section: Optoelectronicsmentioning
confidence: 99%
“…Due to their 2D ultra-thin atomic layer structure, MoS 2 /WS 2 TMDs are shown to exhibit unique physical, optical and electrical properties [4,7]. Their fullerene like nature [8] and their excellent mechanical properties such as friction-reduction and self-lubrication [9] along with their unique optoelectronic properties (UV light absorption [10], band-gap tunability [1,2]) make MoS 2 /WS 2 nanostructures applicable in heterogeneous catalysis, hydrogen storage, lithium-magnesium ion batteries [11,12], various bio-medical applications [9,11,13] and as well as, various electronic and optoelectronic device applications (transistor, photo-transistor and solar cell applications) [2,7,4].…”
Section: Introductionmentioning
confidence: 99%
“…Their fullerene like nature [8] and their excellent mechanical properties such as friction-reduction and self-lubrication [9] along with their unique optoelectronic properties (UV light absorption [10], band-gap tunability [1,2]) make MoS 2 /WS 2 nanostructures applicable in heterogeneous catalysis, hydrogen storage, lithium-magnesium ion batteries [11,12], various bio-medical applications [9,11,13] and as well as, various electronic and optoelectronic device applications (transistor, photo-transistor and solar cell applications) [2,7,4]. Since they possess interesting optoelectonic properties that are tunable by physical layer thickness, various electronic and photonic devices are fabricated based on MoS 2 TMDs, such as hybrid bulk heterojunction solar cells (BHJs) [4], single-layer transistors [2], single-layer phototransistors [7] and back-gated bi-layer fieldeffect transistors [1]. Despite the fact that, single-layer MoS 2 has a large direct bandgap of 1.8 eV and a low electron mobility of 0.5-3 cm…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it was also shown that MoS 2 is a potential candidate in solar cell applications. 17,18 Various properties and possible applications of 2D-MoS 2 and its nanoribbons have also been an active subject of theoretical studies. 19−23 All these recent research results clearly demonstrate that 2D MoS 2 NS present a great potential for nanoelectronic and nanophotonic applications.…”
Section: ■ Introductionmentioning
confidence: 99%